Integrating environmental DNA monitoring to inform eel (Anguilla anguilla) status in freshwaters at their easternmost range—A case study in Cyprus. Issue 2 (27th February 2023) - Griffiths, Nathan P.; Wright, Rosalind M.; Hänfling, Bernd; Bolland, Jonathan D.; Drakou, Katerina; Sellers, Graham S.; Zogaris, Stamatis; Tziortzis, Iakovos; Dörflinger, Gerald; Vasquez, Marlen I.
Abstract: Despite significant population declines and targeted European Union regulations aimed at Anguilla anguilla conservation, little attention has been given to their status at their easternmost range. This study applies wide‐scale integrated monitoring to uncover the present‐day eel distribution in Cyprus' inland freshwaters. These are subject to increasing pressures from water supply requirements and dam construction, as seen throughout the Mediterranean. We applied environmental DNA metabarcoding of water samples to determine A. anguilla distribution in key freshwater catchments. In addition, we present this alongside 10 years of electrofishing/netting data. Refuge traps were also deployed to establish the timing of glass eel recruitment. These outputs are used together, alongside knowledge of the overall fish community and barriers to connectivity, to provide eel conservation and policy insights. This study confirm the presence of A. anguilla in Cyprus' inland freshwaters, with recruitment occurring in March. Eel distribution is restricted to lower elevation areas, and is negatively associated with distance from coast and barriers to connectivity. Many barriers to connectivity are identified, though eels were detected in two reservoirs upstream of dams. The overall fish community varies between freshwater habitat types. Eels are much more widespread in Cyprus than previously thought, yet mostly restricted to lowland intermittent systems. These findings make a case to reconsider the requirement for eel management plans. Environmental DNA‐based data collected in 2020 indicate that "present‐day" eel distribution is representative of 10‐year survey trends. Suggesting that inland freshwaters may act as an unrealized refuge at A. anguilla's easternmost range. Conservation efforts in Mediterranean freshwaters should focus on improving connectivity, therefore enabling eels to access inland perennial refugia. Thus, mitigating the impact of climate change and the growing number of fragmented artificially intermittent river systems. Abstract : This study applies wide‐scale eDNA and catch‐based monitoring to confirm present‐day eel status in Cyprus' inland freshwaters. These methods drew parallel conclusions, finding that eel distribution is mostly restricted to lowland coastal areas, and is negatively associated with migration barriers on the island.